"Keep Government Out of Business": Bank Nationalisation, Financial Reform and The Private Trading Banks In The 1930s. (5th June 2013) - Eather, Warwick; Cottle, Drew
<x xml:space="preserve">Abstract</x> During the early 1930s the private trading banks came under sustained attack from sections of the Australian Labor Party and the Country Party, and from supporters of Major C.H. Douglas. Repeated calls for bank nationalisation or "socialisation of credit" or "social credit" heightened tensions within the banks and conservative political circles. In response, the banks secretly funded a nationwide campaign in support of the Lyons government in the lead‐up to the 1934 federal election. While the campaign was successful, the outcome resulted in the establishment of a Royal Commission to investigate the banking sector. The Royal Commission's recommendations and the Lyons government's proposed banking legislation were about providing greater government control of the sector. Opposition from the Bank of New South Wales and its supporters during the late 1930s helped forestall the legislation. The onset of war and, in 1941, initiatives from the federal Curtin Labor government and the National Security (Wartime Banking Control) Regulations ended what was a decade‐long struggle waged by the trading banks against greater government control of the banking sector.